Epidemiological overview of congenital syphilis in Brazil and Brazilian regions: analysis of the last and the next ten years (Research, Society and Development, 2021)
This paper aims to analyze the overview of Congenital Syphilis (CS) in Brazil and regions, in the last and next decade. This is an ecological study of the years 2009-2018, carried out by the Information System for Notifiable Diseases, analyzing maternal, fetal variables and mortality coefficient (MC). There were registered 158,951 cases of CS in Brazil, mainly in the Southeast (43.0%) and Northeast (30.4%), among women aged 20-29 years (52.5%), with low education (24.2%), who underwent prenatal care (78.6%) and with untreated partners (60.2%). In the next decade, an exponential increase in CS is projected, however with a reduction in MC. There was a higher incidence of CS among newborns of young women, with low education, diagnosed in prenatal care. Recent CS in most of these newborns suggests inadequate treatment for women and partners. Estimates point to syphilis as a persistent public health problem, reflecting low investments in primary care and deficiencies in prenatal care.